Membangun Kesadaran Hukum Bagi Anak Dari Kenakalan Remaja - Elsa Rina Maya Toule; Margie Gladis Sopacua; Astuti Nur Fadillah; Yonna Beatrix Salamor; Leonie Lokollo (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Teenagers as holders of the baton for the next generation of the nation must be maintained in their growth and development. The phenomenon of juvenile delinquency today can be found in society.Purposes of Devotion: Community Service Activities are expected to provide answers about the development of juvenile delinquency and its legal consequences. The purpose of building legal awareness for children from juvenile delinquency is to provide education and understanding of legal regulations relating to children so that children in the future are not affected to commit acts of violence from juvenile delinquency that can lead to legal repercussions or consequences for the child. Method of Devotion: Carrying out legal counseling activities in Erie Hamlet, Nusaniwe Country, Ambon City, Maluku through panel discussions in which the presenters take turns presenting the material then followed by a question and answer session between the presenters and participants.Results of the Devotion: Teenagers as holders of the baton for the next generation of the nation must be maintained in their growth and development. Efforts to tackle juvenile delinquency cannot be done alone, but in overcoming it there must be cooperation between all elements, namely parents, the school, in this case the teacher who acts as a parent in the school, the government and the community.